Corrosion behavior of deformed low-nickel stainless steel in groundwater solution. (April 2019) - Feng, Xingguo; Zhang, Xiangying; Xu, Yiwen; Shi, Ruilong; Lu, Xiangyu; Zhang, Leyuan; Zhang, Jing; Chen, Da
Abstract: Effect of deformation on the corrosion behaviour of 201 low-nickel stainless steel in a simulated groundwater solution was studied via electrochemical tests. The open-circuit potential, pitting potential, polarization resistance and the thickness of passive film decreased with the magnitude of deformation. The carry density of passive film significantly increased as the deformation increasing. In general, the deformation shows a negative effect on the corrosion resistance of the low-nickel stainless steel, which causes the stainless steel more susceptive to pitting in the groundwater. Moreover, the number of pitting initially increased with the magnitude of elastic deformation, while the depths of pitting were extended whereas the number of pitting does not be significantly influenced by the increasing plastic deformation. Highlights: The pitting potential, polarization resistance, thickness of passive film on the low-nickel stainless steel decreased, and the carry density in the passive film increased as the applied strain increasing. The passivity of the stainless steel in the groundwater decreased with the magnitude of deformation. For samples experienced elastic deformation, the number of pitting increased with the strain degree. For the ones suffered plastic deformation, the depth of pitting increased whereas the number of pitting does not significantly change with the magnitude of deformation.